Blockchanging money: reengineering the free world incentive system - Rodrigues, Dário (2022)
Blockchain technology is changing the world incentive system, making programmable money. This kind of money is only fruitful and democratically livable in a transparent political environment. Otherwise, instead of unleashing innovation and collective action with the market’s visible hand of qualified money, the new internet of value will deliver a digital money with the same algorithmic fate that social media met on the previous internet. The latter allows digitizing users’ data and has been used to manipulate consumers and public opinion (possibly in the last two U.S. Presidential elections). Similarly, the former will let states and corporatocracy cross-reference social media and digital money’s data, hurting privacy even more. As blockchains disseminate, having the crucial economic advantage of reducing transaction costs, only free-market competition between private and public blockchains guarantee transparency and democracy. Blockchain technology is the real McCoy, and decentralizing digital money is the free world’s best shot, especially in the new normal triggered by COVID-19.